2021
DOI: 10.24815/ajse.v3i1.19845
|View full text |Cite
|
Sign up to set email alerts
|

Digital Storytelling Video to Analyze Students’ Concept Mastery and Creativity in Learning Food Additives Topic

Abstract: The students have learning difficulties in learning science because their concept mastery and creativity were low. Digital storytelling is good media for students who make their own story. The research was conducted to identify student’s concept mastery and creativity by digital storytelling video in learning food additives. The method used in this research is weak experiment. The sample of 36 students from private school in Cianjur, West Java. The students’ concept mastery was measured by objective test based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…Temuan ini sejalan dengan penelitian Nadia Syavira yang menyoroti kebutuhan siswa akan media pembelajaran berbasis teknologi yang dapat memberikan penjelasan secara interaktif dan dapat digunakan secara berulang kali (Syavira, 2021). Hasil penelitian Putri, Sanjaya, dkk menegaskan bahwa media pembelajaran berfungsi sebagai alat bantu saat proses penyampaian materi pelajaran (Weni Anissa Putri, Yayan Sanjaya, 2021). Temuan ini diperkuat oleh penelitian Putri dan rekan-rekan mengenai kebutuhan keberadaan media pembelajaran interaktif untuk memperkuat pemahaman siswa (N. K. Putri et al, 2021).…”
Section: Pembahasanunclassified
“…Temuan ini sejalan dengan penelitian Nadia Syavira yang menyoroti kebutuhan siswa akan media pembelajaran berbasis teknologi yang dapat memberikan penjelasan secara interaktif dan dapat digunakan secara berulang kali (Syavira, 2021). Hasil penelitian Putri, Sanjaya, dkk menegaskan bahwa media pembelajaran berfungsi sebagai alat bantu saat proses penyampaian materi pelajaran (Weni Anissa Putri, Yayan Sanjaya, 2021). Temuan ini diperkuat oleh penelitian Putri dan rekan-rekan mengenai kebutuhan keberadaan media pembelajaran interaktif untuk memperkuat pemahaman siswa (N. K. Putri et al, 2021).…”
Section: Pembahasanunclassified
“…In this research, analyses of the 40 studies also found that the most comprehensive teaching strategy involving all three creative thinking sub-skills were teaching strategies that incorporated the elements of technology utilization and project-based learning with a science scenario-based approach. For example, studies carried out by Putri et al (2021) andCrǍciun et al (2016) used digital storytelling as an intervention to promote creative thinking skills in the regular science classroom. According to Cheng and Chuang (2019), digital storytelling helps to improve student subs-creative thinking skills through its implementation steps.…”
Section: Teaching Strategy That Comprehensively Focuses On Sub-skills...mentioning
confidence: 99%
“…Therefore, brainstorming orientation can help foster innovation in the organization by focusing the members 'attention on the goal of generating creative ideas (Dominggus et al, 2021). (Peng, 2019) In addition, activities that focused on student centralization by giving autonomy to students to explore the content of knowledge using the help of technology to facilitate the learning process were also recommended (CrǍciun et al, 2016;Hu et al, 2013;Lamb et al, 2015;Muñoz, 2020;Putri et al, 2021). Besides that, the students' understanding of concepts can be further strengthened through dialogues, argumentation or presentation, to help them master science concepts through the process of challenging the proposed ideas (Kumdang et al, 2018;Lee et al, 2013;Vidergor, 2018).…”
Section: Suggested Teaching Activities Should Been Emphasized To Prom...mentioning
confidence: 99%
“…Another approach of the mastery learning model was analysed by Putri and Sanjaya (2021) in a study conducted with a group of 50 eighth-graders from a school in Indonesia who were asked to create some educational videos. The advantages implied by this model are numerous.…”
Section: Adapting Mastery Learning Strategies To Current Learning Con...mentioning
confidence: 99%